Membrane-initiated estrogen receptor-α signaling in osteoblasts is crucial for normal regulation of the cortical bone in female mice - Yiwen Jiang; Karin Horkeby; Petra Henning; Jianyao Wu; Karin H. Nilsson; Lina Lawenius; Sofia Movérare-Skrtic; Priti Gupta; Cecilia Engdahl; Antti Koskela; Juha Tuukkanen; Lei Li; et al. (Bone Research)
Abstract Membrane-initiated estrogen receptor α (mERα) signaling has been shown to affect bone mass in murine models. However, it remains unknown which cell types mediate the mERα-dependent effects on bone. In this study, we generated a novel mouse model with a conditional C451A mutation in Esr1, which enables selective knockout of the palmitoylation site essential for the membrane localization of ERα (C451Af/f). First, we used Runx2-Cre mice to generate Runx2-C451Af/f mice with conditional inactivation of mERα signaling in Runx2-expressing osteoblast lineage cells. No significant changes were observed in body weight, weights of estrogen-responsive organs, or serum concentrations of estradiol between female Runx2-C451Af/f and homozygous C451Af/f littermate controls. High-resolution microcomputed tomography analysis showed a consistent decrease in cortical bone mass in the tibia, femur, and vertebra L5 of Runx2-C451Af/f mice and three-point bending analysis of humerus revealed an impaired mechanical bone strength in Runx2-C451Af/f female mice compared to controls. Additionally, primary osteoblast cultures from mice lacking mERα signaling showed impaired differentiation compared to controls. In contrast, conditional inactivation of mERα signaling in hematopoietic cells, by transplantation of bone marrow from mice lacking mERα signaling in all cells to adult wildtype female mice, did not result in any skeletal alterations. In conclusion, this study demonstrates that mERα signaling in osteoblast lineage cells plays a crucial role in the regulation of cortical bone in female mice and shows that mERα inactivation in hematopoietic cells of adult female mice is dispensable for bone regulation.